Thursday

September 18, 2014

September 18, 2014

Posted by **Monique** on Saturday, August 8, 2009 at 2:04pm.

f(x) = -(x+3)^2, x is greater or less than 3

I know the first thing you do is switch the variables, so it looks like this:

x = -(y+3)^2

Then expand:

x = -y^2-6y-9

And solve for y:

x + 9 = -y^2-6y

I get a little confused after that with y. Help please? Thank you very much!

- Math -
**Monique**, Saturday, August 8, 2009 at 2:04pmoh, i also meant that x is greater than or equal to 3. sorry.

**Answer this Question**

**Related Questions**

Math (repost) - How do find the inverse function for this problem: f(x) = -(x+3...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

Calculus - What is the inverse function of.... f(x) = x^3 - 1 Whats the easiest ...

math - Could you show me step by step how to find the inverse of this problem: ...

Algebra 2 - Find the inverse of the following function: f(x) = 3x + 12 I don't ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

Math 3 - Find the inverse of the function f(x) = 5 – e^(x-1). Determine the ...

pre calculus - Find the inverse of the function below. Graph the function below ...

math help1 - Okay I am a little bit confused about one math question can you ...